Preventive effect of Euphorbia Thymifolia Linn against ethylene glycol-induced urolithiasis in male wistar albino rats - Siva Jyothi CH; Naresh Babu P; Karimulla S.K; Gobinath M (International Journal of Research in Pharmaceutical Sciences, 2023)
The effect of the Ethanolic extract of Euphorbia thymifolia Linn (EEET) against ethylene glycol induced urolithiasis in albino rats is summarized in this study. Lithiasis was induced in rats by administrating 0.75% ethylene glycol in drinking water for 28 days and was manifested by high Urinary calcium, phosphate, oxalate, protein, uric acid, creatinine and low urinary magnesium Content. The EEET was administered in 250 & 500 mg/kg body weight orally for 28 days along with 0.75% ethylene glycol. Results revealed that Urinary calcium, phosphate, oxalate, protein, uric acid, creatinine was reduced and urinary magnesium level was elevated in diseased group. It also increased the urine volume, thereby reducing the tendency for crystallization. The histopathological studies confirmed the induction of lithiasis as microcrystal deposition was observed in section of kidney from animals treated with ethylene glycol. This was reduced, however, after treatment with the extract. These observations enable us to conclude that EEET is effective against ethylene-glycol induced urolithiasis in albino rats.